Development of Audio Visual Health Education Media About Self Management in Patients Type II Diabetes Mellitus - Rifa Ainun Najihah; Nina Indriyawati; Mugi Hartoyo (JENDELA NURSING JOURNAL, 2021)
Background: Self-management in patients with diabetes mellitus (DM) type II aims to control blood sugar levels and prevent the occurrence of disease complications. The media must be able to help understand information. One of the media that can be used is audiovisual that can stimulate vision and hearing senses. Audio Visual Media comes with images, background songs, sounds, and colors so it can cause interest.Purpose: Developing audiovisual about self-management in type II Diabetes Mellitus patients.Methods: This research used RD (research and development) methods with the ADDIE model. This research was only done through the process from analysis, design, and development process with 3 expert validation testing and 10 limited trials. The Analysis of data used is quantitative descriptive with a Likert scale of the value range of 1-5 and qualitative descriptive in the form of comments, suggestions, and criticisms. Results: the results of this study had developed 2 audiovisual videos using Indonesian. Average audiovisual media assessment results from    3    experts    and 10 limited trials got categories worth using.Conclusion: Audiovisual media presents general knowledge material about diabetes mellitus and self-management in type 2 diabetes mellitus patients and is equipped with animated images, backsound music and dubbing material. Audiovisual about self-management in type II diabetes mellitus iscategorized as suitable for use.